2022
DOI: 10.1186/s12909-021-03037-4
|View full text |Cite
|
Sign up to set email alerts
|

“More than just a medical student”: a mixed methods exploration of a structured volunteering programme for undergraduate medical students

Abstract: Background As a result of the COVID-19 pandemic Imperial College School of Medicine developed a structured volunteering programme involving 398 medical students, across eight teaching hospitals. This case study aims to explore the relationship between the processes, context, participant experiences and impacts of the programme so that lessons can be learned for future emergencies and service-learning programmes. Methods Using an illuminative approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…There has been voiced concern that unstructured volunteering may be detrimental to student learning [ 20 ]. However, our research supports the small number of studies from COVID-19 volunteer schemes in acute settings where medical students reported the acquisition of valuable skills [ 14 18 ]. Importantly, GPs also reported that students had a significant impact on clinical care by acting as a vital bridge between the GP and their patients, as they took up these newly adopted ‘para-professional roles’ [ 21 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…There has been voiced concern that unstructured volunteering may be detrimental to student learning [ 20 ]. However, our research supports the small number of studies from COVID-19 volunteer schemes in acute settings where medical students reported the acquisition of valuable skills [ 14 18 ]. Importantly, GPs also reported that students had a significant impact on clinical care by acting as a vital bridge between the GP and their patients, as they took up these newly adopted ‘para-professional roles’ [ 21 ].…”
Section: Discussionsupporting
confidence: 83%
“…By contrast, a study in acute care found that senior student volunteers were more anxious about “working outside their competencies” and of the extra burden that poor performance might place on their clinical team. Whilst early years students with lower expectations were surprised and positive about the impact that they were able to have in their volunteering role [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being capable of helping meant being ready to become a doctor, empowered to be “part of the group”. This empowerment was also observed by Badger et al (Badger et al, 2022 ), who registered that volunteering positively impacted medical students’ well-being and professional identity formation. According to Badger, the “sense of belonging and pride in achievement are drivers of engagement in authentic workplace-based practices and therefore learning”.…”
Section: Discussionsupporting
confidence: 73%
“…In the context of the national lockdowns and government restrictions, this study demonstrated that online volunteering was an overall positive experience, as it offered a space for socialisation, allowed volunteers to gain a sense of fulfilment and provided a convenient and safe option to volunteer. This study is particularly interesting as it demonstrates that many benefits of volunteering [ 14 ] can be obtained online and outside the clinical context. Both modalities were perceived to offer skill development and offer benefits for volunteers’ future professions, especially those interested in paediatrics as a speciality.…”
Section: Discussionmentioning
confidence: 99%